THE EFFECT OF PROFITABILITY, LIQUIDITY, AND SOLVENCY ON FIRM VALUE IN PHARMACEUTICAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2024 - Lola Kambuno; Matdio Siahaan; Wastam Wahyu Hidayat (Yayasan Education and Social Center, 2026)
This study aims to examine the influence of key financial ratios, namely profitability, liquidity, and solvency, on the firm value of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Profitability is measured using Return on Equity (ROE), liquidity is represented by the Current Ratio (CR), and solvency is measured using the Debt to Equity Ratio (DER). Firm value is assessed using the Price to Book Value (PBV) ratio. This research adopts a quantitative approach based on secondary data obtained from the annual financial statements of pharmaceutical sub-sector companies. The sample was selected through a purposive sampling technique according to predetermined criteria. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The findings reveal that profitability (ROE) and solvency (DER) do not have a statistically significant effect on firm value. In contrast, liquidity (CR) has a positive and significant effect on firm value, indicating that stronger short-term financial capability enhances investor confidence and contributes to higher market valuation of pharmaceutical companies during the observation period.